A psychrometric analysis of thermal comfort In low-rise office buildings in Ghana (Journal of Science and Technology, 2016)
A research project on the thermal performance of office buildings in Ghana was conducted and in the process, data loggers were used to record indoor environmental conditions over a period of 12 months in five office buildings. The temperature and relative humidity values recorded were analysed and plotted on psychrometric charts. The results of the study in 15 offices wereplaced in psychrometric charts which showed uncomfortable indoor environmental conditions. The reasons were high relative humidity values, although the temperatures in most of the cases were below 29°C. The impression gained during the observation period was that occupants hadadapted to high humidity levels and therefore found maximum humidity levels of 80% comfortable, provided temperature values did not exceed 29°C. This significant clue calls for further study and the adjustment of the comfort scale for the climatic context of Kumasi, Ghana.